Why Plea Bargains are A Bad Deal for Some. Issue 1 (29th January 2020) - Finkelstein, Michael O.; Levin, Bruce
Abstract: In US federal courts, defendants are often encouraged to plead guilty in exchange for lighter sentences. But not all of those taking a plea might have been found guilty had their cases gone to trial. Michael O. Finkelstein and Bruce Levin estimate the scale of the problem